2018
DOI: 10.1590/1518-8345.2568.3043
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior and sexually transmitted diseases among the female partners of inmates

Abstract: Objective:to analyze the sexual behavior of the female partners of inmates and estimate the prevalence of sexually transmitted diseases. Method:cross-sectional, quantitative study involving 349 female partners of inmates. The Estudo de Comportamento Sexual [Sexual Behavior Study], an instrument validated in Brazil, was used to collect the data. The Statistical Package for the Social Sciences, version 20 was used in the statistical analysis. Results:41.2% of the female partners of inmates reported a prior histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 15 publications
3
24
0
9
Order By: Relevance
“…This fact is consistent with the study conducted by Martins et al in Brazil that assessed the prevalence of STI, demonstrating the lack of condom use in women [25]. It has been concluded that women frequently have no protection and choices regarding their sexual practices because they submit themselves to their partners; thus, they are highly exposed to different types of transmitted diseases [25]. A common example is women living in developing countries who submit themselves to their partners during marital sexual intercourse, making them vulnerable to STI/HIV infection [26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This fact is consistent with the study conducted by Martins et al in Brazil that assessed the prevalence of STI, demonstrating the lack of condom use in women [25]. It has been concluded that women frequently have no protection and choices regarding their sexual practices because they submit themselves to their partners; thus, they are highly exposed to different types of transmitted diseases [25]. A common example is women living in developing countries who submit themselves to their partners during marital sexual intercourse, making them vulnerable to STI/HIV infection [26].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding sexual behaviors, although condom use has not been associated with the presence of STI, it is important to emphasize that more men reported using condoms than women. This fact is consistent with the study conducted by Martins et al in Brazil that assessed the prevalence of STI, demonstrating the lack of condom use in women [25]. It has been concluded that women frequently have no protection and choices regarding their sexual practices because they submit themselves to their partners; thus, they are highly exposed to different types of transmitted diseases [25].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding risky sexual behavior, in the literature, there is a higher prevalence of STI in women partners of inmates due to the higher number of partners, sexual violence, sex for money, or under the influence of alcohol/drugs (7) . Black women also seem to be highly vulnerable to STIs, HIV/AIDS, and the explanatory hypotheses for this evidence are socioeconomic inequalities and institutional racism (8) .…”
Section: Introductionmentioning
confidence: 99%
“…(9) Ademais, o estigma e estereótipos construídos e atribuídos a essas mulheres perpetua as mais diversas expressões de violência em seus cotidianos e as impede de expor suas necessidades e buscar apoio. (10) Estudo realizado com 349 mulheres de apenados, nas três maiores penitenciárias do estado do Paraná, revelou que elas se submetem às ações violentas do parceiro por medo, e algumas são obrigadas a práticas que as expõem a impactos físicos e psicológicos, (11) e também à gravidez indesejada, a Infecções Sexualmente Transmissíveis (IST's), a quadros de depressão, síndrome do pânico, ansiedade e distúrbios psicossomáticos. (12) Outro fator importante é que a maioria das mulheres de apenados é oriunda de áreas carentes, possui baixa escolaridade e dificuldades de inserção no mercado de trabalho.…”
Section: Introductionunclassified